Membina indeks bagi mengukur perlakuan buli di kalangan pelajar sekolah rendah dan menengah - Yahaya, Azizi; Hashim, Shahrin (Faculty of Education, 2008)
The purpose of this study is to identify the level of bullying among secondary and primary schools students in Malaysia based on School Bullying Index. This study also try to identify the type of bullying and its frequency, factor of bullying and characteristic of victims. 1395 secondary and primary school students in the state of Johor, Melaka, Negeri Sembilan dan Selangor have been chosen as the respondents. The sampling has been done using the cluster on cluster random sampling method. A set of School Bullying Index questionnaires was used in this study. Reliability value of the instruments was α = 0.87. Descriptive statistic – frequency, percentages, mean and standard deviation is used to analyze the level and type of bullying and School Bullying Index. The inferencial statistic- t-test is used to analyze the difference of bullying behaviour and Bullying Index between school level, school location and gender. Pearson correlation are used to analyze the relation between the factor of bullying and school bullying index. Results showed, overall level of bullying among school students in four states are low. School bullying index is 38.81. There is no significance difference on bullying behaviour between secondary and primary school and male and female students. There is no significance difference on Bullying Index between secondary and primary school; urban and rural school; and male and female students. Pearson correlation analyze showed that there were significance relation between factor of bullying and bullying index (p=0.005, r=0.103). Based on research finding, suggestion was made to use School Bullying Index as a method to measure level of bullying among students and how successful your intervention programmes against bullying.